New developments in medicinal chemistry - Gil, Irene C.; Ortega, Marta P. (Nova Science Publishers, 2009)
Medicinal or pharmaceutical chemistry is a scientific discipline at the intersection of chemistry and pharmacology involved with designing, synthesising and developing pharmaceutical drugs. This book presents research from around the world in this frontal field